Systemic and topical antibiotics for chronic rhinosinusitis - Burton, M; Head, K; Chong, L; Piromchai, P; Hopkins, C; Philpott, C; Schilder, A (Cochrane Collaboration, 2015)
Review question: We reviewed the evidence for the benefits and harms of systemic (given by mouth) or topical (given by nose) antibiotics for people with chronic rhinosinusitis. Background: Chronic rhinosinusitis is a common condition that is defined as inflammation of the nose and paranasal sinuses (a group of air-filled spaces behind the nose, eyes and cheeks). Patients experience at least two or more of the following symptoms for at least 12 weeks: blocked nose, discharge from their nose or runny nose, pain or pressure in their face and/or a reduced sense of smell (hyposmia). Some people will also have nasal polyps, which are grape-like swellings of the normal nasal lining inside the nasal passage and sinuses. Study characteristics: We included five randomised controlled trials (RCTs) with a total of 293 participants. The studies were small (43 to 79 participants). Four recruited adults and the fifth children. Three studies only included people with chronic rhinosinusitis without nasal polyps, one a mix of people with and without polyps and the remaining study only people with polyps. All used different types of oral antibiotics; none looked at topical antibiotics. The antibiotics were given to patients as either antimicrobial or anti-inflammatory agents and for different lengths of time, although in all cases we were able to look at the outcomes after three months. Antibiotics were compared with placebo, with intranasal (in the nose) steroids or with oral steroids. One study used antibiotics as an additional treatment, on top of nasal saline irrigation and most people also took intranasal steroids in this study. Key results and quality of the evidence: When compared to a placebo (three studies), there was moderate quality evidence in one study that there may be an improvement in disease-specific health-related quality of life (HRQL) with oral antibiotics in people with chronic rhinosinusitis (without polyps) at the end of treatment (three months), but it is unclear if HRQL was still improved three months later. There may have been an increase in gastrointestinal disturbances and suspected allergic reaction (rash or skin irritation) with antibiotics but we are very uncertain and the quality of the evidence is very low. Antibiotics were used alongside nasal saline irrigation and intranasal steroids (compared to placebo plus the same) in one study. It is not clear if there was an important difference in disease-specific HRQL after treatment (three months) or at three months after treatment was completed (low quality evidence). There may have been more people in the antibiotics group who felt they had 'improved' at the end of treatment, but there were also people who had worse symptoms in both groups (very low quality evidence). It is very uncertain if there was a difference in gastrointestinal disturbances between groups. When compared with intranasal steroids in people with chronic rhinosinusitis (without polyps), it was very uncertain if there was a difference in disease severity (using a combined score for four different symptoms) between the antibiotics and intranasal steroids groups in one study (low quality evidence). No information was given about adverse events. The one study that compared antibiotics with oral steroids (in people with chronic rhinosinusitis with polyps) did not present any effectiveness results that we could use. It was uncertain if there was any difference in gastrointestinal disturbances or skin irritation in the antibiotics group (very low quality evidence). There were no reports of any serious adverse effects in any of the studies. Conclusions: We found very little evidence that oral antibiotics are effective in patients with chronic rhinosinusitis. We did find moderate quality evidence of a modest improvement in disease-specific quality of life in adults with chronic rhinosinusitis without polyps receiving three months of a macrolide antibiotic. The size of the improvement was moderate (0.5 points on a five-point scale) and only seen at the end of the three-month treatment; by three months later no difference was found. Despite a general understanding that antibiotics can be associated with adverse effects, including gastrointestinal disturbances, the results in this review were very uncertain because the studies were small and few events were reported. More research in this area, particularly evaluating longer-term outcomes and adverse effects, is required.